Roads to the temple : truth, memory, ideas, and ideals in the making of the Russian revolution, 1987-1991 - Aron, Leon Rabinovich (Yale University Press, 2012)
Leon Aron considers the "mystery of the Soviet collapse" and finds answers in the intellectual and moral self-scrutiny of glasnost that brought about a profound shift in values. Reviewing the entire output of the key glasnost outlets in 1987-1991, he elucidates and documents key themes in this national soul-searching and the "ultimate" questions that sparked moral awakening of a great nation: "Who are we? How do we live honorably? What is a dignified relationship between man and state? How do we atone for the moral breakdown of Stalinism?"Contributing both to the theory of revolutions and history of ideas, Aron presents a thorough and original narrative about new ideas' dissemination through the various media of the former Soviet Union. Aron shows how, reaching every corner of the nation, these ideas destroyed the moral foundation of the Soviet state, de-legitimized it and made its collapse inevitable.